Lembaga Pendidikan Integratif: Sinergi Aspek Akademik, Keahlian, Moral, Kewirausahaan, dan Komunitas Religius - Muhammad Yacub (Universitas Negeri Malang, 2016)
Most Islamic boarding schools (pondok pesantren) are private educational institutions and had been institutionalized long before the existence of madrasah and all kinds of western education systems in Indonesia. The Islamic boarding schools perform themselves as centers for developing Indonesian man-power, inoculating the spirit of enterpreneurship, organizing agro-religious tourism activities, and developing strong relationships or good cynergetic activities with members of community surrounding the pesantren's. To develop and organize new schools or universities in the future, we can adopt the spirit of self-help or self-support as the heart of pesantren's doctrine. In other words, the essence of pesantren's system can be implemented in our system of national education